Optimalisasi Penggunaan Anggaran Dana Desa dalam Pembangunan dan Pelayanan Sarana dan Prasarana Masyarakat Pada Desa Madongka Kecamatan Lakudo Kabupaten Buton Tengah - Manan Sailan; Herman Herman; Sukri Badaruddin (Seminar Nasional LP2M UNM, 2022)
Abstract. The problem that will be studied in this study is how to optimize the use of the Village Fund Budget in the Development and Service of Community Facilities and Infrastructure in Madongka Village, Lakudo District, Central Buton Regency. The research method used is a qualitative type of research method. Which aims to search and collect data through interviews with a number of individuals or groups of informants who are competent in understanding the meaning behind the facts, as well as using a phenomenological approach. The data collection technique is carried out using interview methods and documentation. The data analysis technique in this study was carried out descriptively qualitatively, which refers to several stages, namely (1) Data condensation, (2) Data presentation (data display), (3) Drawing conclusions or verification. The results of this study are the management of the village fund budget for the construction and service of community facilities and infrastructure in Madongka Village, Lakudo District, Central Buton Regency, starting from the planning and implementation stages. At the planning stage, judging from the musrembang process held by the village government, it is still very low, due to the lack of information distribution submitted by village officials to the people of Madongka village. Meanwhile, at the implementation stage, based on the results of the research, it is less effective, where the use of the village fund budget can be resolved properly and optimally but due to the lack of transparency of information related to the implementation of activities by the village government to the village community, the achievement of the objectives of managing the village fund budget is considered less effective Keywords: Village Fund Budget, Development, Service, Facilities and Infrastructure